"Evaluation OF The Application Of The Change Management In Higher Education Institutions (A Field Study In Tishreen University)" (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The objective of this research project is to study the range of application of the dimensions of the change management (change management in human resources, change management in technology, change management in the organizational structure, change management in strategic) in Tishreen university, and to achieve the objectives of this research, the questionnaires were distributed to managers and administrative staff , volume of the sample studied were (345) individuals,( 327 ) of them were valid for analysis to collect data and to examine the range of the applications of these dimensions, we used SPSS program, in addition we interviewed many employees from administrative staff and managers To make a general view about reality of the work. One of the most important results was the reduction in change level for the four dimensions , therefore Tishreen University lacks the basic Requirement of a change in human resources , the absence of a change in the technology used, the lack of in strategic change management and lack of change management in organizational structure for the university studied and the lack of change in for members of the sample examined. هدف هذا البحث إلى دراسة مدى تطبيق أبعاد إدارة التغيير(إدارة التغيير في الموارد البشرية، إدارة التغيير في التكنولوجيا، إدارة التغيير في الهيكل التنظيمي، إدارة التغيير في الاستراتيجية والأهداف) في جامعة تشرين، ولتحقيق أهداف الدِّراسة تمَّ توزيع استبانة على المديرين والعاملين الإداريين وقد بلغ حجم العينة المدروسة (345) وكان منها صالحاً للتحليل(327) استبانة لجمع البيانات ولدراسة مدى تطبيق هذه الأبعاد، وتمَّ الاعتماد على البرنامج الإحصائي spss، بالإضافة إلى قيام الباحث بالعديد من المقابلات مع العاملين الإداريين والمديرين للتعرُّف على واقع العمل أكثر، وكان من أبرز النتائج التي تمَّ التوصل إليها أنَّ هناك انخفاض في مستوى التغيير بالنسبة للأبعاد الأربعة وبالتالي جامعة تشرين تفتقر لمقومات نشوء تغيير في مواردها البشرية وكذلك عدم وجود تغيير في وسائل التكنولوجيا المستخدمة وأيضاً عدم وجود تغيير في الهيكل التنظيمي بالنسبة للجامعة وعدم التغيير في الاستراتيجية والأهداف الموكلة بالنسبة لأفراد العينة المدروسة.